Fostering Quality Education Through Learning Models: Evidence from Problem-Based and Cooperative Learning with Interpersonal Intelligence on Students’ Learning Outcomes - Iman Sampurna; Asep Muhyidin; Lukman Nulhakim (Postgraduate, University of Mataram, 2026)
This study examines differences in student learning outcomes based on learning models (Problem-Based Learning and Cooperative Learning) and students’ levels of interpersonal intelligence. This study employed a quasi-experimental design using a 2 × 3 factorial framework. This research was conducted in the 2nd semester of the elementary school teacher education study program, the Basic Concepts of Basic Science/Social Studies course at Setiabudi Rangkasbitung University in Banten Province. A total of 100 students participated in the study, with each group including fifty students. The sampling method used, cluster random sampling. The interpersonal intelligence instrument uses a questionnaire with a Likert scale of 1-5 and the learning outcomes of the instrument are multiple choice pre- and post-test questions. This study yielded three main findings. There was a significant difference in learning outcomes between students taught using different learning models (PBL vs Cooperative), as indicated by an F-value of 10.739 and a significance level of p < 0.001. There were also significant differences in learning outcomes among students with high, medium, and low levels of interpersonal intelligence, as shown by an F-value of 23.419 and a significance level of p < 0.001. In addition, there was a significant interaction effect between the learning model and students’ levels of interpersonal intelligence on learning outcomes, as evidenced by an F-value of 8.357 and a significance level of p< 0.006. This study implies that the choice of learning model plays a crucial role in improving learning outcomes, as problem-based learning and cooperative learning contribute in different ways.